Effect of Boron Carbide Particles Addition on the Mechanical and Wear Behavior of Aluminium Alloy Composites - null Ravindra; M. Rajesh; K. Dilip Kumar; Mamunuri Sailender; G. Pathalinga Prasad; N. Nagaraj; Perumalla Janaki Ramulu (Advances in Materials Science and Engineering)
In this research, synthesis and assessment of the mechanical and wear possessions of Al7049-nano B4C composites are determined by experiments. Using the liquid metallurgy route, a stir casting technique was used to create composites with increasing concentrations of nano B4C from 3 to 9 weight %. Each composite’s reinforcement particles were heated to 400 degrees Celsius before being added to the molten Al7049 alloy in two separate steps, i.e., two-stage stir casting to optimise wettability and distribution. Scanning electron microscopy (SEM) was utilised to examine the microstructure, and energy dispersive spectroscopy (EDS) was utilised to determine the elemental make-up. Mechanical characteristics of composites were determined by subjecting them to tensile, compression, and hardness tests. Wear tests were conducted as per ASTM G99 standards with varying loads and speeds. Nanosized B4C particles were found to be dispersed throughout the sample space in a microstructural analysis. Hardness, ultimate strength, yield strength, and compression strength of Al7049 alloy composites were found to increase significantly as the weight percentage of nano B4C was increased. Additionally, compared to the unreinforced form, the ductility of the Al7049 alloy composites was slightly reduced. SEM micrographs of tensile-fractured specimens were used for research into the field of tensile fractography. Nano B4C reinforced composites exhibited superior wear resistance as compared to Al7049 alloy. These prepared composites can be used for wing root fitting of an aircraft.